Erlotinib Salvage Therapy in Pulmonary Adenocarcinoma Patients With Disease Progression After Previous EGFR-TKI Treatment. (December 2016) - Wu, Wen-Shuo; Wu, Chieh-Hung; Lai, Shinn-Liang; Chiu, Chao-Hua; Shih, Jen-Fu; Lee, Yu-Chin; Chen, Yuh-Min
Abstract : Background: Erlotinib is an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) with promising efficacy in treating pulmonary adenocarcinoma. Treatment choices are few when patients with pulmonary adenocarcinoma have failed both EGFR-TKI and chemotherapy. The purpose of this study was to demonstrate the efficacy of erlotinib as salvage treatment for these nonresponsive patients. Methods: We retrospectively reviewed the chart records of our stage IV pulmonary adenocarcinoma patients who were diagnosed and treated between July 2004 and June 2013. Clinical data, including type of response to treatment, time to disease progression, duration between the end of first-line EGFR-TKI treatment and starting erlotinib treatment, and overall survival time, were collected. Results: A total of 98 patients were enrolled, and all had been treated with EGFR-TKI, either as a first-line therapy or following platinum-based chemotherapy; of them, 60 patients had a response to initial EGFR-TKI treatment. All received erlotinib as salvage treatment after their disease had progressed following EGFR-TKI treatment. Ninety-three (93.3%) patients had also received previous platinum-based chemotherapy. The median progression-free survival with erlotinib as salvage treatment for patients with and without a response to front-line EGFR-TKI was 4.9 and 3.4 months ( P =0.869), respectively. The progression-free survival with erlotinib treatment in the sensitizing EGFR mutation group was 4.3 months, and in the EGFR wild-type group it was 2.6 months ( P =0.22). Conclusions: In pulmonary adenocarcinoma patients who had been heavily treated, erlotinib could still be a choice, regardless of the EGFR mutation status, or whether the patients had responded to previous EGFR-TKI treatment.